1994
DOI: 10.1002/ijc.2910560220
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effects of monoclonal antibody g250, interferons and tumor necrosis factor, in mice with renal‐cell carcinoma xenografts

Abstract: Because renal-cell carcinoma (RCC) is considered relatively resistant to radio- and chemotherapy, RCC patients may benefit from new treatment modalities, e.g. immunotherapy. In vitro and in vivo studies suggest that combinations of cytokines such as interferon gamma or interferon alpha (IFN-gamma, IFN-alpha) and tumor necrosis factor alpha (TNF-alpha) may act synergistically. In this study we tested whether a monoclonal antibody (MAb) G250, reactive with a RCC-associated antigen, showed anti-tumor effects in v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

1994
1994
2003
2003

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 21 publications
1
17
0
Order By: Relevance
“…The G250 antigen is an attractive target for antibodymediated therapy, because of its nearly exclusive expression in renal carcinoma cells. Studies with the G250 MAb and the murine bispecific G250/OKT-3 (anti-CD3) MAb have shown preferential localisation of these antibodies to the tumour (Oosterwijk et al, 1993;van Dijk et al, 1991) and antitumour effects in RCC-xenografted nude mice (van Dijk et al, 1994). The G250/anti-CD3 MAb was chimerised to decrease immunogenicity of the bispecific antibody in patients, because studies in patients with murine anti-tumour antibodies and bispecific antibodies are limited by the development of HAMA responses.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The G250 antigen is an attractive target for antibodymediated therapy, because of its nearly exclusive expression in renal carcinoma cells. Studies with the G250 MAb and the murine bispecific G250/OKT-3 (anti-CD3) MAb have shown preferential localisation of these antibodies to the tumour (Oosterwijk et al, 1993;van Dijk et al, 1991) and antitumour effects in RCC-xenografted nude mice (van Dijk et al, 1994). The G250/anti-CD3 MAb was chimerised to decrease immunogenicity of the bispecific antibody in patients, because studies in patients with murine anti-tumour antibodies and bispecific antibodies are limited by the development of HAMA responses.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of a third peak representing parental anti-CD3 MAb was not the result of the loss of either the anti-CD3 MAb heavy or light chain, since RT-PCR analysis showed the presence of mRNA for all four antibody chains. The chromatographic separation method has been used previously to purify bispecific OVTL3/OKT-3 MAb ( van Ravenswaay Claasen et al, 1993), murine bispecific OC/TR (Warnaar et al, 1994), chimeric bispecific OC/TR (Coney et al, 1996) and murine bispecific G250/OKT-3 MAb (van Dijk et al, 1989), and was shown to separate all combinations of heavy and light chains into distinguishable peaks. Therefore, we expect peak 2 of the chimeric G250/anti-CD3 MAb separation to contain IgG molecules composed of the parental heavy and light chains.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations